Pendidikan Agama Katolik di Sekolah Katolik Mayoritas Agama Budha - Elelia Elelia (VOCAT: JURNAL PENDIDIKAN KATOLIK, 2022)
SMA Santo Ignatius Singkawang is not the only private school in the city of Singkawang, but this private school is one of the Catholic schools in the city of Singkawang. The subject of Catholic Religious Education at SMA Santo Ignasius Singkawang is not something that is foreign to the public and non-Catholic students. SMA Santo Ignasius Singkawang majority of students are Buddhist. In learning, especially religious lessons taught at SMA Santo Ignasius Singkawang are Catholic Religion Lessons. Even though the majority of students are Buddhist, they do not show disrespect towards Catholic religious lessons at school or outside of school. In fact, through learning Catholicism, they are able to instill an attitude of tolerance towards other religions in school. The objectives to be achieved in this study are to improve learning achievement, communicate interactions, and engage and live the faith of students, teachers and employees. Because in Catholic religious education and good character in schools, churches, families and communities, the main key is love.